2006
DOI: 10.1242/jcs.03162
|View full text |Cite
|
Sign up to set email alerts
|

Low peak bone mass and attenuated anabolic response to parathyroid hormone in mice with an osteoblast-specific deletion of connexin43

Abstract: Connexin43 (Cx43) is involved in bone development, but its role in adult bone homeostasis remains unknown. To overcome the postnatal lethality of Cx43 null mutation, we generated mice with selective osteoblast ablation of Cx43, obtained using a Cx43fl allele and a 2.3-kb fragment of the α1(I) collagen promoter to drive Cre in osteoblasts (ColCre). Conditionally osteoblast-deleted ColCre;Cx43–/fl mice show no malformations at birth, but develop low peak bone mass and remain osteopenic with age, exhibiting reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
249
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(282 citation statements)
references
References 62 publications
27
249
6
Order By: Relevance
“…These Cx43-deficient mice die at birth because of a defect in cardiac function (Reaume et al, 1995). Recently, conditional deletion of Cx43 in cells of osteogenic lineage has revealed an important role for Cx43 in postnatal skeletal homeostasis as well (Chung et al, 2006). These conditional Cx43 knockout mice, which use a 2.3-kb collagen I promoter-driven Cre-recombinase to excise a floxed Cx43 allele in cells of the osteoblast lineage, exhibit severe osteopenia as a result of defective osteoblast function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Cx43-deficient mice die at birth because of a defect in cardiac function (Reaume et al, 1995). Recently, conditional deletion of Cx43 in cells of osteogenic lineage has revealed an important role for Cx43 in postnatal skeletal homeostasis as well (Chung et al, 2006). These conditional Cx43 knockout mice, which use a 2.3-kb collagen I promoter-driven Cre-recombinase to excise a floxed Cx43 allele in cells of the osteoblast lineage, exhibit severe osteopenia as a result of defective osteoblast function.…”
Section: Introductionmentioning
confidence: 99%
“…There is both in vivo and in vitro evidence that manipulating the relative abundance of Cx43 can affect osteoblast function. A gene dosage effect is observed using a model of conditional knockout of Cx43 in osteoblasts, as the anabolic response to PTH in heterozygous Cx43 Ϫ/fl mice is intermediate between wild-type and Cx43 conditionally deleted animals (Chung et al, 2006). Similarly, heterozygous Cx43 Ϫ/fl mice demonstrate an intermediate response to mechanical load (Grimston et al, 2008).…”
mentioning
confidence: 99%
“…calcium ions, inositol phosphates and cyclic nucleotides) to pass from cell to cell [9,10]. Several researchers have described the existence of gap junctions between bone cells [11,12]. Although other connexins can be expressed in osteoblastic cells, gap-junctional intercellular communication between these cells correlates best with Cx43 expression.…”
Section: Connexin43mentioning
confidence: 99%
“…It has been shown that Cx43 is abundantly expressed in both osteoblasts and osteocytes, where it can transmit hormonal signals, mechanical load and growth factor cues among cells to coordinate the synthesis of new bone [19]. Over the past two decades, many studies have described a role for Cx43 intercellular communication in the proliferation and differentiation of osteoblasts and bone cells [11,12,[20][21][22]. Recently, conditional deletion of Cx43 in cells of osteogenic lineage has revealed an Indeed, we detected a significant up-regulation of Cx43 in OPLL ligament fibroblasts at 12 and 24 h after mechanical strain loading in comparison with static conditions, and there were no changes in non-OPLL cells.…”
Section: Connexin43mentioning
confidence: 99%
See 1 more Smart Citation